Особливості впровадження сучасного освітлення в навчальних аудиторіях - Скорюкова, Яніна Германівна; Марков, Сергій Михайлович (Vinnytsia National Technical University, 2019)
The article substantiates the need to introduce modern lighting. The main characteristics of LED lamps of the most well-known domestic manufacturers regarding the possibility of their use in classrooms have been analyzed. The light distribution was simulated by the example of a real classroom using the DIALux program.